Caribean Museum in Barranquilla: Regional identity in the space of simulacrum (2011)
This article explores on the imagined identity that the Museo del Caribe communicates and whether or not it contributes to the construction of citizenship. Presented as the first regional museum in Colombia, the paper examines whether the proposed cultura